2020
DOI: 10.1002/tox.22988
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits oral squamous cell carcinoma cells proliferation while promoting apoptosis through inhibition of CBX7 protein

Abstract: As a natural compound, resveratrol (Res) is confirmed to be promising drug for the treatment of malignant tumors. Therefore, our study aimed to observe the impacts of Res on the proliferation and apoptosis of oral squamous cell carcinoma cells (HSC-3 cells) as well as the mechanism involving chromobox protein homolog 7 (CBX7) signal transduction. HSC-3 cells were treated with Res, Akt agonist (AL3818) and p16 inhibitor (SC79), and transfected with CBX7 mimics and inhibitor plasmids. The CCK-8 assay was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Furthermore, resveratrol has been demonstrated to overcome cetuximab-resistance in OSCC by targeting urokinase-type plasminogen activator receptor [43]. Additionally, extensive observations have also reported that resveratrol suppressed the growth of OSCC cells by regulating chromobox protein homolog 7 (CBX7) signal transduction, inducing mitochondrial apoptosis and G2/M phase cell cycle arrest, and inhibiting epithelial-mesenchymal transition [44][45][46]. However, the association among resveratrol and MAGEA12 has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, resveratrol has been demonstrated to overcome cetuximab-resistance in OSCC by targeting urokinase-type plasminogen activator receptor [43]. Additionally, extensive observations have also reported that resveratrol suppressed the growth of OSCC cells by regulating chromobox protein homolog 7 (CBX7) signal transduction, inducing mitochondrial apoptosis and G2/M phase cell cycle arrest, and inhibiting epithelial-mesenchymal transition [44][45][46]. However, the association among resveratrol and MAGEA12 has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A dose-dependent decrease in cell viability was also observed after treatment of H-357 cells with resveratrol [41]. Chen et al treated HSC-3 cells with different concentrations (0,15,30,60, and 90 μM) at different time points and found that the number of cells in G1 phase increased and cells in S and G2 phases decreased [27]. In conclusion, resveratrol is expected to become a new drug for the treatment of OSCC through the regulation of cell cycle function.…”
Section: Resveratrol Regulates the Cell Cycle Of Oral Cancermentioning
confidence: 94%
“…Resveratrol significantly induced the expression of the proapoptotic gene BAD in OEC-M1 cells [25] , and inhibited thyroid hormone-induced antiapoptotic activity by inhibiting death ligand 1 (PD-L1) expression [26], also inhibited the proliferation and induced apoptosis of oral squamous cell carcinoma cells by inhibiting CBX 7/Akt and activating the p16 cascade [27].…”
Section: Resveratrol Induces Autophagy and Apoptosis In Oral Cancer C...mentioning
confidence: 99%
“…A chimera composed of the CBX5 protein fused to the estrogen receptor-DNA-binding domain and AR-ligand-binding domain is an effective transcriptional inhibitor and participates in the gene silencing effect associated with long-term 4-hydroxytamoxifen (OHT) therapy, inducing drug resistance to OHT (235). Resveratrol inhibits the proliferation of oral squamous cell carcinoma and induces apoptosis by inhibiting CBX7/AKT and activating the p16 signaling pathway (236). The retention of CBX7 decreases lung cancer cell proliferation (at least partially through the downregulation of phosphorylated ERK and phosphorylated p38) and increases the apoptosis rate after irinotecan and etoposide therapy (at least partially through the downregulation of Bcl-2, phosphorylated AKT and phosphorylated JNK) (237).…”
Section: Cancer Therapies Targeting Cbxsmentioning
confidence: 99%